2011
DOI: 10.1371/journal.pone.0025542
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Agonists Synergize with CD40L to Induce Either Proliferation or Plasma Cell Differentiation of Mouse B Cells

Abstract: In a classical dogma, pathogens are sensed (via recognition of Pathogen Associated Molecular Patterns (PAMPs)) by innate immune cells that in turn activate adaptive immune cells. However, recent data showed that TLRs (Toll Like Receptors), the most characterized class of Pattern Recognition Receptors, are also expressed by adaptive immune B cells. B cells play an important role in protective immunity essentially by differentiating into antibody-secreting cells (ASC). This differentiation requires at least two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 49 publications
2
42
0
1
Order By: Relevance
“…Injection of various TLR agonists has been shown to impact B cell activation and/or proliferation. For example, injection of TLR3 agonists, in synergy with BCR signaling and CD40L, aids in B cell activation and proliferation, whereas TLR7 agonists promote development of antibody-secreting cells (43). Previous studies using virus infection models have shown that early B cell activation in draining lymph nodes as manifested by surface expression of CD69 and CD86 occurs within the first few days after infection, is polyclonal, and is transient (26,44).…”
Section: Discussionmentioning
confidence: 99%
“…Injection of various TLR agonists has been shown to impact B cell activation and/or proliferation. For example, injection of TLR3 agonists, in synergy with BCR signaling and CD40L, aids in B cell activation and proliferation, whereas TLR7 agonists promote development of antibody-secreting cells (43). Previous studies using virus infection models have shown that early B cell activation in draining lymph nodes as manifested by surface expression of CD69 and CD86 occurs within the first few days after infection, is polyclonal, and is transient (26,44).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, TLR activation and T cell help might interact to induce somatic mutation. TLR activation of B cells can enhance antigen presentation and increase surface expression of co-stimulatory molecules, which will facilitate non-antigen-specific interaction with T cells (76,77). Therefore, TLR activation can enhance somatic mutations in T cell-dependent or -independent B cell responses.…”
Section: Tlr Engagement and T Cell-independent B Cell Activationmentioning
confidence: 99%
“…The subsequent cascade signal induces type I interferons (IFN-␣/␀) and production of inflammatory cytokines (31). Of these PRRs, TLR7 is important not only for the activation of the innate antiviral response but also for the induction of adaptive immunity (7,22,25,27,34,35). Heer and colleagues showed that TLR7 signaling is critical for antibody isotype class switching (22).…”
mentioning
confidence: 99%
“…Recently, we have shown that TLR7 signaling is involved in the recruitment of myeloid-derived suppressor cells (MDSCs) and for the shaping of humoral immu-nity in response to IAV infection (27). Boeglin and colleagues later showed that a combination of B-cell receptor, CD40, and TLR7 stimulation on B cells augments antibody-secreting cell (ASC) differentiation (7). Collectively, these data suggest that TLR7 signaling is important in adaptive immunity, particularly in the enhancement of B-cell responses.…”
mentioning
confidence: 99%